2010
DOI: 10.1021/jf903434h
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tobacco Mosaic Virus (TMV) Quassinoids from Brucea javanica (L.) Merr.

Abstract: Two new quassinoids, javanicolide E (1) and javanicolide F (2), along with fifteen known C-20 quassinoids were isolated from the seeds of Brucea javanica (L.) Merr. The antitobacco mosaic virus (TMV) activity of these quassinoids was screened by the conventional half-leaf and leaf-disk method along with Western blot analysis. All of the seventeen quassinoids showed potent anti-TMV activity. Among them, eight compounds, brusatol (3), bruceine B (4), bruceoside B (5), yadanzioside I (6), yadanzioside L (7), bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 22 publications
0
83
0
Order By: Relevance
“…Although some studies have demonstrated that NNM has the good anti-TMV bioactivity [13,14] and enhanced the some resistance enzymes activity in tobacco [15], the mechanism involved in this antiviral activity has not been well understood. In the current study, this knowledge provides further insight into this expanding area on the mechanism of NNM against the plant virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have demonstrated that NNM has the good anti-TMV bioactivity [13,14] and enhanced the some resistance enzymes activity in tobacco [15], the mechanism involved in this antiviral activity has not been well understood. In the current study, this knowledge provides further insight into this expanding area on the mechanism of NNM against the plant virus.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pollution-free microbial pesticide characterized by broad spectrum, high-efficiency, low toxicity and lesspersistent and enhances resistance in host plants by destruction of CP [11]. It have also been shown that NNM generally exhibits antimicrobial activity against TMV [12][13][14] and promotes PAL, POD and SOD activity which results in the markedly enhancement of plant resistance against TMV [15]. However, the antiviral activity of NNM and the underlying mechanisms in plant resistance are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the half-leaf method has been commonly used to assay the inactivation activity of chemicals in NNM comparisons (Chen et al, 2009;Yan et al, 2010). Almost all the literature on TMV control included in this review reports on how the half-leaf method can be applied.…”
Section: Changes In Evaluation Methodsmentioning
confidence: 99%
“…The Anti TMV activity was tested using the half-leaf method. 13 The inhibitory activity of the compounds against TMV replication were tested using two approaches. First, the half-leaf method was used to test the antiviral activity in the local lesion host Nicotiana glutinosa in vivo.…”
Section: Methodsmentioning
confidence: 99%